Pulmonary toxicity in patients receiving docetaxel chemotherapy - CEYHAN, BERRİN; DANE, FAYSAL; YUMUK, PERRAN FULDEN (HUMANA PRESS INC, 2010)
Pulmonary toxicity can rarely be seen with cytotoxic agents. We aimed at investigating the pulmonary toxicity of docetaxel in patients other than lung carcinoma. Forty patients were investigated prospectively. Spirometry, DLCO and high-resolution computed tomography (HRCT) scans were applied to all patients before and 14-21 days after completion of docetaxel. We used a HRCT scoring system that was based on the previous studies. We have seen no pulmonary symptoms that may reflect pulmonary toxicity. There were statistically significant differences between pre- and post-treatment values of FEV1 (L/s), FEV1/FVC (%), DLCO/VA (DLCO/L), DLCO/VA (%) (P < 0.05), FEF25-75 (L/s), FEF25-75 (%) (P < 0.01), DLCO (mL/mmHg/min), DLCO (%) (P < 0.001), Also, there was a statistically significant difference between the pre- and post-treatment HRCT scores. There was a statistical relationship between post-treatment HRCT scores, number of docetaxel cycles (r = 0.49, P < 0.0001) and docetaxel cumulative dose (r = 0.61, P < 0.0001). Docetaxel caused a significant decline in pulmonary function tests (PFTs) and progression in HRCT scores but the symptoms of patients were not consistent with these differences. The negative effects of docetaxel on PFTs and HRCT scores should be investigated more reliably by increasing the number of patients with further studies.
Keywords: Docetaxel; Drug effects; Lung; Neoplasia; Pneumonitis; Toxicity; CELL LUNG-CANCER; THIN-SECTION CT; BREAST-CANCER; INTERSTITIAL PNEUMONITIS; ANTINEOPLASTIC AGENTS; COMPUTED-TOMOGRAPHY; RADIATION-THERAPY; FUNCTION TESTS; PHASE-II; PACLITAXEL